MAKNA PENGGUNAAN CADAR SEBAGAI IDENTITAS KEAGAMAAN DI KALANGAN MAHASISWI INSTITUT SYEKH ABDUL HALIM HASAN BINJAI - Vinky Raisyah; Aulia Kamal (UIN Sumatera Utara Medan, 2026)
This study aims to analyze the meaning of wearing the niqab as a religious identity among female students at Institut Syekh Abdul Halim Hasan (INSAN) Binjai through Peter L. Berger and Thomas Luckmann's social construction theory. The research gap lies in the scarcity of studies that consistently apply the externalization-objectivation-internalization framework to explain how niqab meaning is built, sustained, and negotiated at a locally rooted Islamic institute, rather than merely describing personal motives. This study employed a qualitative phenomenological design involving twelve niqab-wearing female students as primary informants and three non-niqab female students as supporting informants. Data were collected through in-depth interviews, four rounds of field observation, and documentation, then analyzed using the Miles, Huberman, and Saldana interactive model. The findings reveal three main points. First, the decision to wear the niqab is shaped by religious study, family, peers, religious figures, and life experiences such as accidents, threatened harassment, and pandemic-related anxiety, alongside personal awareness. Second, social construction unfolds through externalization, in which religious values are articulated into the act of wearing the niqab; objectivation, in which the niqab becomes an institutionalized social fact provoking both acceptance and stigma, including labels such as ninja and accusations of radicalism; and internalization, in which the niqab is absorbed into self-identity, although some informants still show situational negotiation or even social withdrawal. Third, the niqab is interpreted as obedience to Allah, a guardian of honor, a vehicle for hijrah toward self-improvement, and a religious identity demanding moral responsibility. Theoretically, this study extends the application of social construction theory to contemporary religious practice by revealing variation in the pace and depth of internalization across individuals. Practically, the findings are expected to inform inclusive campus policy and to help society understand the niqab more fully, without judgment based on appearance alone.